New copolymer of poly(N‐vinylcarbazole) and poly(p‐phenylenevinylene) for optoelectronic devices. Issue 4 (8th June 2013) - Mbarek, Mohamed; Massuyeau, Florian; Duvail, Jean‐Luc; Wery, Jany; Faulques, Eric; Alimi, Kamel
ABSTRACT A novel diblock copolymer based on poly(N‐vinylcarbazole) PVK and poly(p‐phenylenevinylene) (PPV) precursor was synthesized by oxidative cross‐linking. The grafting of PPV with PVK moieties was elucidated by infrared absorption analysis. A structural study by X‐ray diffraction and a morphological study of the copolymer by scanning and transmission electron microscopy reveal a multiscale one‐dimensional self‐organization both at the molecular and at the sub‐micrometric level. The resulting copolymer exhibits original optical properties compared to those of PVK and PPV ones and presents an improved thermal behavior. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 2839–2847, 2013